Frequently asked questions : trade in agricultural goods, Barbados - Turnbull, Allan (Ministry of Foreign Affairs and Foreign Trade. Foreign Trade Division St. MichaelBB, 2007)
Provides brief answers to some of the more frequently asked questions on the World Trade Organization (WTO) agreements concerning international trade in agricultural goods. Deals with issues ranging from the basic principles of the World Trade Organization; the WTO rules for agriculture, market access, domestic support, export subsidies, and human, animal and plant health and safety; new developments which affect international rules in trade in agricultural goods; and the possible challenges for Barbados based on these developments